Use Of Artificial Intelligence Technology in Companies in Poland: A Comparative Analysis Of 2023-2024 Period - Ludmiła FILINA-DAWIDOWICZ; Agnieszka BARCZAK; Joanna SĘK; Piotr TROJANOWSKI; Anna WIKTOROWSKA-JASIK (Communications of International Proceedings, 2025)
Currently, there is a rapid development of artificial intelligence technologies that can be applied within enterprises. In Poland, some enterprises have already started to implement these technologies, that is associated with a number of expectations and challenges. The aim of this article is to examine the level of use of artificial intelligence technologies in small, medium and large enterprises operating in Poland. Based on data from the Central Statistical Office for the years 2023 and 2024, a comparative analysis of the use of these technologies by enterprises of different sizes was conducted. An increase in the percentage of enterprises using artificial intelligence technologies has been observed. It is more common for large entities to implement these technologies compared to medium and small ones. In medium and large-sized enterprises, technologies that automate processes or support decision-making are most frequently used. In contrast, an increased interest in technologies that generate written or spoken language in small enterprises was noted. Small and medium-sized enterprises often use these technologies to support marketing or sales, while large enterprises use them to support the production process or the provision of services. Recommendations have been proposed for companies considering to implement artificial intelligence technologies. The results of the research may be of interest to companies operating in various industries interested in using the technologies analyzed.
Keywords: artificial intelligence technologies; companies; recommendations